ENHANCING NEGOTIATION SKILLS WITHIN EDUCATIONAL SETTING - Karapetyan, Anna (Armenian Folia Anglistika, 2024)
The study of negotiation skills within education extends beyond verbal communication to encompass cultural competence. Language instruction not only facilitates language acquisition but also fosters development of negotiation skills. Thus, the focus of the present study is on integrating negotiation skills training within the framework of English language instruction, in higher education in particular. The investigation carried out with the application of qualitative and quantitative research methodology, investigates the role of negotiation in educational contexts, discusses the significance of integrating negotiation skills training into higher education, evaluates the effectiveness of various teaching methods in enhancing students’ negotiation abilities, examines the relationship between negotiation and language acquisition. As a result, it can be stated that the integration of negotiation training into the education classroom holds immense potential for students (both academically and personally) in today’s globalized world, thus representing not only an educational imperative but also a societal necessity enabling students to navigate confidently in today’s increasingly complex and interconnected world.